POS0953 COMPARING LONG-TERM PERSISTENCE RATES OF SECUKINUMAB OR ADALIMUMAB USING PROPENSITY SCORE MATCHING IN PATIENTS WITH PSORIATIC ARTHRITIS: FINDINGS FROM THE REAL-WORLD FLYWAY STUDY - Ishii, K.; Kameda, H.; Kiriyama, J.; Mikami, T.; Uratsuji, H.; Morita, A. (Annals of the rheumatic diseases, 2024)
Background:Psoriatic arthritis (PsA) is a chronic disease, and treatment persistence is a crucial indicator of optimal therapy outcomes. Understanding factors influencing drug survival is essential for maintaining a long-term treatment response. Commonly used biologics for PsA include Secukinumab (SEC), an IL-17A inhibitor, and Adalimumab (ADA), a TNF-alpha inhibitor. However, few studies have confirmed the persistence of SEC in PsA in Japan, and there are few scientifically based comparisons of long-term persistence, demographic, and clinical characteristics for these biologics.Objectives:The primary objective of this study was to estimate the 1-year persistence rate of SEC in PsA patients, filling the gap in studies on SEC persistence in Japan. Key secondary and exploratory objectives included comparing persistence rates and usefulness rates of SEC and ADA at different time points (at 24 weeks, 1 year, 2 years, and 3 years).Methods:This was a retrospective non-interventional cohort study with secondary use of data from Medical Data Vision, a hospital-based database in Japan. Patients aged 18 years or older who were diagnosed with PsA and given a prescription of SEC or ADA at least once during the inclusion period from February 2015 to September 2020 were included. The primary endpoint was the prescription-based 1-year persistence rate of SEC. Secondary and exploratory endpoints included comparing persistence rates between SEC and ADA and assessing usefulness rates with reference to past criteria[1]. Propensity score matching was performed to compare them between SEC and ADA.Results:The study included 182 patients in the SEC group and 352 in the ADA group. The 1-year persistence rate for SEC was 68.3%. After 1:1 propensity score matching was conducted, 171 patients from each group were included. The mean age in the SEC and ADA groups were 55.8 ± 14.1(SD) and 56.0 ± 14.7(SD), respectively, with male subject proportions of 48.5% and 45.6%, and bio-naive status proportions of 66.7% and 62.0%, respectively. There were no significant differences in patient background between the two groups after matching. At 24 weeks, persistence rates were 78.7% (SEC) and 67.4% (ADA), while at 3 years, rates were 41.2% (SEC) and 25.5% (ADA) (p-value=0.002; log-rank test) (Figure 1). The median persistence time was 27.8 months for SEC and 12.5 months for ADA. SEC patients consistently exhibited higher usefulness rates at all timepoints, ranging from 41.1% to 47.0%, compared to ADA patients, who showed rates between 18.4% and 31.3% (Table 1).Conclusion:Our study showed 1-year SEC persistence rates in the real world for patients with PsA in Japan. Patients treated with SEC exhibited higher persistence and usefulness compared to those treated with ADA.REFERENCES:[1] Zhang H. et al. RMD Open 2021; 7: e001399Figure 1.Secukinumab and Adalimumab persistence rates Kaplan-Meier curveLog rank test: 0.002Table 1.Secukinumab and Adalimumab usefulness ratesTreatment usefulnessnSecukinumab(n=171)nAdalimumab(n=171)p-valueAt 24 weeks12953 (41.1%)11235 (31.3%)0.11At 1 year10047 (47.0%)8118 (22.2%)0.001At 2 years5323 (43.4%)387 (18.4%)0.012At 3 years2611 (42.3%)195 (26.3%)0.27Acknowledgements:Putnam PHMRDisclosure of Interests:Kentaro Ishii Employee of Novartis, Hideto Kameda Speaker bureau: AbbVie, Asahi Kasei, Astrazeneca, Boehringer, Bristol-Myers, Eisai, Eli Lilly, Janssen, Mitsubishi-Tanabe, Novartis, Pfizer, UCB, consultant: AbbVie, Sanofi, Grant/research support: Asahi Kasei, Boehringer, Chugai, Eisai, Mitsubishi-Tanabe, Pfizer, Taisho, Junna Kiriyama Employee of Novartis, Toshiaki Mikami Employee of Novartis, Hideya Uratsuji Employee of Maruho, Akimichi Morita Speakers bureau: AbbVie, Boehringer Ingelheim, Bristol Myers Squibb, Celgene, Eisai, Eli Lilly, Janssen, Kyowa Hakko Kirin, LEO Pharma, Maruho, Nippon Kayaku, Novartis, Pfizer, Sun Pharma, Taiho Pharma, Torii Pharma, UCB Pharma, Ushio, Consultant: AbbVie, Boehringer Ingelheim, BristoMyers Squibb, Eli Lilly, Janssen, Kyowa Hakko Kirin, Maruho, Novartis, Pfizer, UCB Pharma, Grant/research support: AbbVie, Boehringer Ingelheim, Eisai, Eli Lilly, Janssen, Kyowa Hakko Kirin, LEO Pharma, Maruho, Novartis, Sun Pharma, Taiho Pharma, Torii Pharma, UCB Pharma, Ushio